If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 5 = 5(1 + 2x) Reorder the terms: 5 + 10x = 5(1 + 2x) 5 + 10x = (1 * 5 + 2x * 5) 5 + 10x = (5 + 10x) Add '-5' to each side of the equation. 5 + -5 + 10x = 5 + -5 + 10x Combine like terms: 5 + -5 = 0 0 + 10x = 5 + -5 + 10x 10x = 5 + -5 + 10x Combine like terms: 5 + -5 = 0 10x = 0 + 10x 10x = 10x Add '-10x' to each side of the equation. 10x + -10x = 10x + -10x Combine like terms: 10x + -10x = 0 0 = 10x + -10x Combine like terms: 10x + -10x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 16+7r-8+7r=8r+5r | | 3(p-3)+7=32-4(2p+5) | | 4.5(x+7)=41.85 | | 34-6x=6-10x | | 4x+11=-49-6x | | (-8+3i)+(-5i)= | | 2+11x=-48+x | | X+12yi=3-6i | | (2x+1)(3-x)=0 | | 3(4x-1.5)-2x=17 | | 8*(x-2)=32 | | 9+4*x=29 | | 315=7(6m+3) | | 12-3*x=3 | | -2x-4=32 | | 7x-17=6x+7 | | (X+6)+x+2x=35 | | .333x-4=2 | | 2*(y^2)-x^2=0 | | -2(12)+12y=47 | | -16x+7=-41 | | -2(-12)+12y=47 | | 2(x+7)+3(x-5)= | | .09X+X=100 | | -48-12x=8 | | -2(-2)+12y=47 | | 7n-3n=19 | | 4i^5= | | -2c(-c-12)=-2c-12 | | -5(7x-9)=-35x+45 | | -8x-2=-x+3 | | 368=-7x+8(-5x-1) |